2005
DOI: 10.1162/1088198054084699
|View full text |Cite
|
Sign up to set email alerts
|

Using Input‐Output Analysis to Measure the Environmental Pressure of Consumption at Different Spatial Levels

Abstract: SummaryInput-output modeling is a useful tool for tracing environmental impacts of consumption. Because it includes impacts originating from production layers of infinite order (capturing the entire economy), input-output modeling is highly relevant for studies operating in a life-cycle context. In this article we show how the input-output approach can be used to enumerate the problem of sustainable consumption. Based on a literature survey including research done by the authors we present measures of the emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(68 citation statements)
references
References 60 publications
1
61
0
6
Order By: Relevance
“…This indicated that the influence of demographic effects on household energy is limited if population is under control. These findings are basically the same as the conclusion of Fu et al [38], Lenzen et al [18,39] and Munksgaard et al [40].…”
Section: Results and Discussion Of Lmdi Modelsupporting
confidence: 92%
“…This indicated that the influence of demographic effects on household energy is limited if population is under control. These findings are basically the same as the conclusion of Fu et al [38], Lenzen et al [18,39] and Munksgaard et al [40].…”
Section: Results and Discussion Of Lmdi Modelsupporting
confidence: 92%
“…EIO-LCA thus enables an analyst to consider the environmental effects throughout the economy (i.e., the direct and indirect effects across the supply chain) that result from a change in output for a particular industry (2). Several other works have expanded on the EIO-LCA framework such as that conducted by Suh on hybrid models (22,23) and by several research groups on multi-regional models (13,24,25). National EIO-LCA Models.…”
Section: Methodsmentioning
confidence: 99%
“…While many studies explore the carbon emissions embedded in trade, 4 some studies focus specifi cally on the role of imported goods and services and their associated emissions in the carbon footprints of households 5 (Hertwich and Peters 2009 ;Lenzen et al 2006 ;Munksgaard et al 2005 ;Nijdam et al 2005 ;Peters and Hertwich 2006b ). Peters and Hertwich ( 2006a ) put forward a general rule that countries with a high proportion of imports and relatively clean electricity generation are likely to have a signifi cant proportion of their household carbon emissions attributed to imports.…”
Section: Consumption Accounting and Carbon Footprintingmentioning
confidence: 99%
“…However, the defi nition of what is included in a carbon footprint is contentious, as shown in Table 9.1 . In this chapter 4 See for example: Davis and Caldeira ( 2010 ), Ahmad and Wyckoff ( 2003 ), Andrew et al ( 2013 ), Atkinson et al ( 2011 ), Cave andBlomquist ( 2008 ), Hertwich and Peters ( 2009 ), Lin and Sun ( 2010 ), Maenpaa and Siikavirta ( 2007 ), Munksgaard et al ( 2005 ), Nakano et al ( 2009 ), Peters and Hertwich ( 2008b ), Peters et al ( 2011 ), Shui and Hariss ( 2006 ), Weber and Peters ( 2009 ) and Knight and Schor ( 2014 ). 5 Consumption accounting attributes carbon emissions to the 'fi nal demand' of a country and is based on the UN System of National Accounts.…”
Section: Consumption Accounting and Carbon Footprintingmentioning
confidence: 99%
See 1 more Smart Citation